2005
DOI: 10.1111/j.1539-6924.2005.00650.x
|View full text |Cite
|
Sign up to set email alerts
|

A Benefit‐Cost Analysis of Retrofitting Diesel Vehicles with Particulate Filters in the Mexico City Metropolitan Area

Abstract: In the Mexico City metropolitan area, poor air quality is a public health concern. Diesel vehicles contribute significantly to the emissions that are most harmful to health. Harmful diesel emissions can be reduced by retrofitting vehicles with one of several technologies, including diesel particulate filters. We quantified the social costs and benefits, including health benefits, of retrofitting diesel vehicles in Mexico City with catalyzed diesel particulate filters, actively regenerating diesel particulate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…(2) Studies comparing iF estimated using this model have found similar results compared with studies using empirical data or complex air-dispersion models. 11,12 (3) Because this type of model is widely used, 2628 the results reported here can be directly applied as model input parameters. (4) The one-compartment model is readily scaled in size for each location studied.…”
Section: Methodsmentioning
confidence: 99%
“…(2) Studies comparing iF estimated using this model have found similar results compared with studies using empirical data or complex air-dispersion models. 11,12 (3) Because this type of model is widely used, 2628 the results reported here can be directly applied as model input parameters. (4) The one-compartment model is readily scaled in size for each location studied.…”
Section: Methodsmentioning
confidence: 99%
“…The iF concept has been increasingly used in risk and health impact assessment studies to summarize exposure parameters and to predict exposure in those areas with limited data . In particular, the life‐cycle impact assessment (LCIA) field has adopted and developed the iF concept to predict exposure to various stressors in LCIA studies .…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have predicted iFs for secondary particles, but all of these studies have focused on long‐range transport of particles. Only two of the previously mentioned iF studies have predicted intraurban iFs for secondary particles . Secondary particles are formed in the air through the oxidation of SO 2 , NO x , and VOC gases and, due to the time needed for the oxidation process, the concentrations of secondary particles are lower near the emission sources than respective concentrations of primary particles (per unit of emission).…”
Section: Introductionmentioning
confidence: 99%
“…Using actuarial-risk estimates, the estimated coefficients of the fatal and non-fatal risk variables are about 15% smaller when both risk variables are included (column (3) of Table 2), suggesting little omitted-variable bias in columns (1) and (2). In contrast, using both perceived-risk variables (column (3) of Table 3), the estimated coefficient on the fatal-risk variable is insignificant and negative and the coefficient on the non-fatal-risk variable is larger than when the fatal-risk variable is omitted (column (2) of Table 3), which suggests that estimates including both perceived-risk variables are influenced by colinearity and are unreliable.…”
Section: Resultsmentioning
confidence: 99%
“…Although many estimates of the monetary value of health risk have been obtained for the United States and other higher-income countries, few such estimates exist for lowerincome countries and so analysts conducting benefit-cost analyses for these countries often extrapolate from values obtained in other coun-tries (e.g. [1,2]) or use human-capital estimates (e.g. [3]) rather than theoretically preferred willingness-to-pay values.…”
Section: Introductionmentioning
confidence: 99%